PERMAINAN EDUKATIF UNTUK MENINGKATKAN KEMAMPUAN BERBAHASA MANDARIN SISWA SEKOLAH MINGGU METTAYANA BUDDHIST CENTRE - Nuriani (LPPM Universitas Cipta Mandiri, 2025)
This research aims to improve the Mandarin language skills of Sunday Buddhist Class’ students at Mettayana Buddhist Center, Medan, by enhancing their interest and learning motivation through an educational game approach with a lotus flower theme (莲花 liánhuā). The method used is classroom action research (CAR). The subjects of the research were 20 students aged between 7 and 12 years old. The results of the study showed that educational games such as Mandarin character flashcards (汉字 Hànzì), lotus flower-themed Mandarin puzzles, and origami paper lotus flower folding activities significantly improve students' interest, motivation, participation in learning. Consequently, students’ mastery of vocabulary and Mandarin pronunciation also improved significantly. This study recommends an educational game learning approach based on Buddhist values ​​in Mandarin language education for students of Sunday Buddhist Class.